Resilience and mental health in university students post-COVID-19 pandemic: insights from the Republic of Cyprus - Magorokosho, Natasja Kudzai; Heraclides, Alexandros; Papaleontiou-Louca, Eleonora; Prodromou, Maria (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic profoundly affected higher education globally. While the immediate psychological effects of the pandemic are well-documented, the long-term impacts on mental health and the potential moderating role of resilience among this population, remain understudied.MethodsThis cross-sectional study aimed to explore the complex interplay between the impact of the COVID-19 pandemic, resilience, and the multifaceted mental health outcomes experienced by university students in the Republic of Cyprus during the post-pandemic era. Participants were from the 4 major districts (Nicosia, Limassol, Larnaca, Paphos) and data was collected between April–July 2024. Three validated scales were used to assess the overall impact of the COVID-19 pandemic (Covid Impact Scale; CIS), mental health symptoms (Symptom Checklist 90-Revised; SCL-90-R), and resilience (Connor-Davidson Resilience Scale; CDRISC), among a sample of 1,017 students. Linear regression analysis was conducted to determine the associations among COVID-19 impact, resilience and mental health.ResultsHigher COVID-19 Impact was associated with poorer mental health (β = 2.54, p < 0.001). Higher resilience was associated with lower COVID-19 Impact (β = −0.08, p < 0.001). Moderation analysis revealed that among students with high resilience, COVID-19 Impact was more strongly associated with worse mental health (β = 3.09, p < 0.001) compared to students with low resilience (β = 1.52, p < 0.001). Resilience was significantly associated with mental health (β = −0.31, p < 0.001).ConclusionThe COVID-19 pandemic had a significant and persistent negative impact on the mental health of Cypriot university students, even after the end of the pandemic, which was profound even among students with high resilience. Further research is needed to better understand the long-term implications of major health crises and to identify effective interventions to promote resilience and mental well-being.